RELATIONSHIP BETWEEN FUNCTIONAL STATUS, NATRIURETIC PEPTIDE LEVELS AND ECHOCARDIOGRAPHIC PARAMETERS IN PATIENTS WITH PRECAPILLARY PULMONARY HYPERTENSION: Imaging and functional status in pulmonary hypertension - Stankovic, Ivan; Grujičić, Katarina; Cerović, Milivoje; Vranić, Ivona; Gaković, Branka; Panić, Miloš; Cvjetan, Radosava; Zlatković, Marina; Raspopović, Srđan; Nešković, Aleksandar N. (Medical Research, 2023)
Introduction/Aim While echocardiography plays an important role in the follow-up of patients with precapillary pulmonary hypertension (PH), several studies have identified World Health Organisation functional class (WHO FC), 6-minute walk distance (6MWD) and N-terminal prohormone of brain natriuretic peptide (NT-proBNP) as the strongest prognostic markers. We investigated the relationship between echocardiographic indices, functional status and NT-proBNP in patients with precapillary PH. Material and Methods A total of 23 patients were included in this retrospective study. Data were collected from routine risk assessments, including WHO FC, 6MWD, NT-proBNP, standard, strain and three-dimensional echocardiography. The echocardiographic data were analysed in terms of the patients’ functional status as determined by WHO FC, 6MWD and NT-proBNP values. Results Patients in WHO FC III or IV had a shorter 6MWD [180 (interquartile range 85-240 m)] than patients in WHO FC I or II [409 (interquartile range 364-494 m), p=0.02)], while the difference in NT-proBNP was not statistically significant [FC I or II: 1297 (interquartile range 283-3196) versus FC III or IV: 343 (interquartile range 274-598) pg/ml, p=0.146]. There were inverse correlations between 6MWD and left and right ventricular longitudinal strain and a direct correlation between 6MWD and pulmonary acceleration time (r=0.73; p=0.001). NT-proBNP measurements were directly correlated with right heart dimensions and right ventricular strain and inversely correlated with pulmonary acceleration time (r=-0.70; p=0.004). Conclusion Standard and advanced echocardiographic indices of right ventricular structure, function and hemodynamics correlate with functional status and natriuretic peptide levels in a heterogeneous cohort of patients with precapillary PH.